ANALISIS PERENCANAAN STRATEGS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK WARD DAN PEPPARD STUDI KASUS: FAKULTAS KOMPUTER UMITRA INDONESIA - Ahmad Ikhwan; Romi Hendri (Universitas Mitra Indonesia, 2020)
AbstractThree main objectives of the application of IS / IT in an organization. First, improve work efficiency by automating various processes that manage information. Second, improve management effectiveness by satisfying information needs for decision making. Third, improve competitiveness or improve organizational competitive advantage by changing the style and way of doing business. These three goals can be achieved optimally if there is a guarantee of alignment between the IS / IT strategy and the organization's business strategy, where later the business strategy will provide direction for achieving an organizational goal, and the IS / IT strategy will provide support to the achievement of the organization's goals through the preparation of IT infrastructure in accordance with the organization's business strategy. To determine IS / IT strategies that can support the achievement of the organization's vision and mission, it is necessary to understand the organization's business strategy through IS / IT strategic planning, which will be explained through the stages of IS / IT strategic planning based on the Ward and Peppard methodology.